Potential of the daycent model to predict change in greenhouse gas emissions with cessation of tillage for cultivation of perennial energy crops - Thomas, Amy; Hiscock, Kevin; Bond, Alan (Agrociencia Uruguay, 2012)
Bioenergy may make up a signiﬁ cant proportion of future renewable energy supplies, and for perennial feedstocks, this will require conversion of land to a no till (NT) system. Previous studies suggest that NT leads to increased soil organic matter (SOM) storage, which breaks down over time resulting in increased N2O emissions. This may not indicate net total increase, since indirect emissions from eroded SOM with tillage should be considered. Given the high global warming potential of N2O, it is crucial to predict net change in emissions rather than focusing only on potential for C storage. The DayCent model has been used to represent both tilled [1, 2], and untilled [3, 4] agroecosystems. This study assesses its suitability to represent land conversion to NT; ﬁ rst by exploring model structure and process representation, and secondly by using sensitivity analysis to identify whether DayCent matches published variation between tillage regimes. DayCent predicts increasing surface and slow-decomposing soil carbon for no till, but not the expected increase in N2O emissions. It has been suggested that changes in soil structure with tillage affect inﬁ ltration, and therefore nitriﬁ cation and denitriﬁ cation processes leading to N2O emissions [5, 6]. For accurate simulation of the relationship to precipitation, DayCent should ideally represent differing soil water capacity (SWC) and porosity between tillage regimes, and the impacts on water ﬁlled pore space (WFPS). DayCent also fails to appropriately respond to low C:N ratio residue applications, or to simulate interaction between tillage and nutrient applications. Recommendations are provided for improvements to DayCent to resolve these issues and enable more robust scenario analysis. Assuming improved performance at validation, this should facilitate more accurate carbon equivalent emissions for land use change, incorporating N2O.